The impact of FX exposure on the firm’s stock market price - Bondarenko, Mariia; Brůna, Karel, 1973-; Tesařová, Žaneta; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
This research aims to analyze the possible impact of exchange rate changes on the stock return of 208 European companies during the period from 2012 to 2018, additionally examining how this impact differs across companies of different size, operating in various industries. For testing, two wide group of sectors were chosen: industrial, including manufacturing and construction companies, and service sectors of economy, consisting of wholesale and retail, tourism and other industries. Multiple regressions with stock return as a dependent variable, and such explanatory variables as changes in exchange rate, market risk premium, inflation, cost of borrowing, profitability, capital structure and growth prospects of the company were used to test underlying hypotheses of this research along with determination of key predictors of stock price behavior. Empirical results confirm that there is a statistically significant link between changes in exchange rate and stock return, and that medium-size companies as well as firm operating in service sector of economy are more exposed to this impact.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses